A Rare Case of Typical Carcinoid of Lung - Deodhar, Anand; Kulkarni, Dinesh (Medical Science: Trends and Innovations Vol. 3, 2025)
The lung is the second most common site for carcinoid tumors after the gastrointestinal tract and accounts for 30% of neuroendocrine tumors in the body. This study offers a comprehensive review of the Typical Carcinoid of Lung. A sixty-year-old male clinically presented with complaints of recurrent cough, intermittent chest pain and breathlessness for the last three months. High-resolution computerized tomography (HRCT) showed a single well-defined 22x27 mm heterogeneously enhancing nodule in the left paracardiac region, suggesting it to be a metastatic deposit. IHC was carried on paraffin blocks for Neuron specific enolase, Synaptophysin and Chromogranin which were positive while Pancytokeratin showed focal weak positivity; Ki-67 was positive and Vimentin was negative and thus confirming our diagnosis of Low Grade Typical Carcinoid. Neuroendocrine tumors represent 25% of primary lung neoplasms, of which only 2% are typical carcinoids. 75% of lung carcinoids originate from Kulchitsky cells in bronchus. Typical carcinoid tumors are well differentiated with low-grade malignancy. Strong and diffuse positivity for neuroendocrine markers CD 56, synaptophysin and chromogranin is exhibited by these tumor cells. Carcinoid tumors in the past were excluded from TNM staging but the 7th edition of the TNM staging system includes carcinoids. The patients are usually younger than for usual lung cancers. Carcinoid syndrome is usually absent when the tumor is confined to the lung. Markedly different prognoses and treatments underlie the importance of accurate pathologic diagnosis of neuroendocrine tumors of the lung. Typical carcinoid has a five-year survival up to 95% when there is complete surgical excision. Lung-sparing resections as a primary treatment are adequate and complete resection yields long-term survival. The role of adjuvant chemotherapy or radiotherapy has not been well documented.